The Overview Effect and Creative Performance in Extreme Human Environments - White, William Frank (Frontiers in Psychology, 2021)
The Overview Effect is usually seen as a shift in worldview that occurs when astronauts view the Earth from orbit or on lunar missions. This is an accurate understanding of the phenomenon, but it does not include any references to how the experience might affect astronaut performance while in the extreme environment of outer space. In this paper, we suggest some potential avenues of research to determine a potential link between the Overview Effect and creative performance.